Genetic Innovation Science Group: Evaluation Report - Paz Ybarnegaray, R.; Haussmann, B.I.G.; Meyer, D.H.; Bryan, G.J.; Asare, S.E. (2024)
The CGIAR 2030 Research and Innovation Strategy sets the stage for research that provides solutions for development. Priorities set out in the strategy were delivered through 33 initiatives grouped within three interlinked Action Areas: Systems Transformation, Resilient Agri-food Systems, and Genetic Innovation (GI).